The Cotton Sector of India: A Brief Study: Economic Impact of World Cotton Prices on Poverty in India (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This paper assesses the effects of world cotton prices on poverty among India’s cotton-producing households. This paper provides a discussion of the poverty line for India as well as estimates of the national levels of rural and urban poverty and the decline of those levels from 1973–1974 to 2004–2005.